2021
DOI: 10.1016/j.asmr.2021.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Superior Gluteal Reconstruction Results in Promising Outcomes for Massive Abductor Tendon Tears

Abstract: To evaluate the 1-year outcomes of a small patient series following open gluteus medius/minimus repair with human dermal allograft incorporated into the repair construct using a double-row repair. Methods: Data from consecutive patients undergoing a superior gluteal reconstruction for massive, irreparable abductor tendon tears with severe tendon loss and atrophy by a single fellowship trained surgeon from January 2018 to May 2019 were collected and analyzed. Baseline demographic data and magnetic resonance ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…There is currently no gold standard for repair of hip abductor tears. Techniques that have been described to date include repair augmentation with acellular dermal matrix, reconstruction with Achilles allograft and various isolated or combined tendon transfer techniques involving the gluteus maximus, TFL or vastus lateralis [ 9 , 10 , 17–20 ]. Tendon transfer and augmentation have multiple benefits.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no gold standard for repair of hip abductor tears. Techniques that have been described to date include repair augmentation with acellular dermal matrix, reconstruction with Achilles allograft and various isolated or combined tendon transfer techniques involving the gluteus maximus, TFL or vastus lateralis [ 9 , 10 , 17–20 ]. Tendon transfer and augmentation have multiple benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, indications for allograft use are related to tendon quality, where there is concern for ability to achieve a robust repair in the operating room (OR). 2,7 In this case, given the complete tear with large amount of tendon retraction on preoperative MRI, it was decided allograft augmentation would be utilized.…”
Section: Video Transcriptmentioning
confidence: 99%
“…Outcome studies are currently limited, but a 2021 study of 8 patients who underwent abductor reconstruction with a dermal allograft found no re-tears at 1-year follow-up, with 75% of patients above Patient Acceptable Symptomatic State based on the modified Harris Hip score (mHHS). 2…”
Section: Video Transcriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Reconstruction provides an option when the tendon is too degenerated or retracted for primary repair and would result in high tension with risk of surgical failure. In 2021, Browning et al evaluated the 1-year outcomes in a small series of patients who underwent superior gluteal reconstruction (SGR) for irreparable abductor tendon tears 66 . They described using human dermal allograft secured by a DR technique, and at the 1-year follow-up, SGR had favorable patient-reported outcomes with no evidence of retears.…”
Section: Augmentation and Reconstruction Techniquesmentioning
confidence: 99%